Property-Owning Democracy And Global Justice - Hazenberg,Haye (2015)
How do we justify property-owning democracy from a global justice perspec-tive? This short paper outlines a diverse array of domestic justifications for property-owning democracy, and relates them to recent developments in the study of international inequality and international trade. It finds that far from there being an opposition between the domestic and the global demands of distributive justice, these can actually be construed as complementary. While an open economy is the best guarantee for continuing the rise in living stand-ards in poor countries and the decline in global inequality, the rise in domestic inequality threatens to derail the project of a globally intertwined economy. Property-owning democracy, as defended by Rawls, is suggested as a timely corrective to the rise of domestic inequality, and defended over and above both welfare-state capitalism and liberal socialism as the preferred path to-wards greater global distributive justice.